Accuracy of core biopsy image-guided post-neoadjuvant chemotherapy breast to predict pathologic complete response - P. V. Krivorotko; V. V. Mortada; R. S. Pesotskiy; A. S. Artemyeva; A. S. Emelyanov; S. S. Ereshchenko; G. A. Dashyan; N. S. Amirov; T. T. Tabagua; L. P. Gigolaeva; A. V. Komyakhov; K. S. Nikolaev; et al. (Опухоли женской репродуктивной системы)
Background. Achieving a pathologic complete response (pCR) after neoadjuvant systemic therapy (NST) is a predictive factor for improving disease free and overall survival. In triple negative (TN) and HER2-positive breast cancer (BC), the pCR rate exceeds 60 %. Patients with TN and HER2-positive BC who demonstrate an excellent response to NST are likely ideal candidates for downsizing surgery. The condition for reducing the volume of surgical intervention is a reliable determination of pathologic complete response using instrumental imaging and biopsy methods.Aim. To further assess the accuracy of post-NST image-guided biopsy to predict pCR.Materials and methods. Sixty one patients with T1-3N0-3 triple negative or HER2-positive BC receiving NST in the Department of Breast Tumors of the NMRC of Oncology named after N.N. Petrov in the period from 2017 to 2019 were enrolled in this single-center retrospective trial. Patients underwent ultrasound-guided core-biopsy of the initial breast tumor region before surgery. Findings were compared with findings on pathologic evaluation of surgical specimens to determine the performance of biopsy in predicting pCR after NST.Results. After neoadjuvant systemic therapy, clinical partial response (cPR) was diagnosed in 47 (77 %) patients, clinical complete response (cCR) in 14 (23 %) patients. pCR in the core-biopsy tissue and surgical material was achieved in 46 (75.4 %) and 37 (60.7 %), respectively. Performance of image-guided core-biopsy: sensitivity 100 % (95 % confldence interval (CI) 90.51-100), specificity 62.5 % (95 % CI 40.59-81.20), false-negative rate (FNR) 0 %, positive-predictive value (PPV) 75.00 % (95 % CI 59.46-85.99), negative predictive value (NPV) 100.00 %.Conclusion. This retrospective trial showed that ultrasound-guided core biopsies are accurate enough to identify breast pCR in patients with triple-negative or HER2-positive BC with good response after NST (FNR 0 %). Based on these results, a prospective clinical trial has commenced in which breast surgery is omitted in patients with a breast pCR after NST according to image-guided biopsy.